Investigating the Relationship Between Brand Experience Dimensions and Brand Resonance Through Two Different Brands Selected from the Cosmetics and Food Sectors - GUNDUZYELI, Bora (International Journal of Contemporary Economics and Administrative Sciences, 2022)
In today’s global competitive environment, where the functional benefits of products and services converge, the concept of experience has become increasingly important for brands in creating customer loyalty. In the present study, the effects of sensory, affective, behavioral and intellectual dimensions of brand experience on brand resonance, which represents a high level of active loyalty and interaction in the brand-customer relationship, were examined through two brands selected from two different sectors. The research was carried out using the survey method by reaching a total of 465 people who are users of the relevant brands. In the analysis of the collected data, it was aimed to determine the effect of different dimensions of brand experience on brand resonance separately, and to compare the results by repeating the analysis for both brands. The results obtained in the study show that affective, behavioral and intellectual experiences had a significant effect on brand resonance in both selected brands, while sensory experience dimension did not make a statistically significant contribution to explaining brand resonance.